IMPACT OF PHYTOESTROGENS ON ENDOCRINE GLANDS OF CT OF PHYTOESTROGENS ON ENDOCRINE GLANDS OF ALBINO RATS II. ADRENAL - EMMA R. SERAPHIM; M. P. SINHA (The Bioscan, 2010)
It is clearly proved that the oxalis corniculata has steroidogenic activity and this natural chemical can be safely used as it does not alters the functioning of organs which is proved by its action on one of the endocrine organ - adrenal gland, which functions normally in the extract treated female albino rat.